2016
DOI: 10.1002/bies.201600043
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Kadenbach: Electron flux rate through cytochrome c‐oxidase determines the ATP‐inhibitory effect and subsequent production of ROS

Abstract: Mitochondrial respiration is the predominant source of ATP. Excessive rates of electron transport cause a higher production of harmful reactive oxygen species (ROS). There are two regulatory mechanisms known. The first, according to Mitchel, is dependent on the mitochondrial membrane potential that drives ATP synthase for ATP production, and the second, the Kadenbach mechanism, is focussed on the binding of ATP to Cytochrome c Oxidase (CytOx) at high ATP/ADP ratios, which results in an allosteric conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 147 publications
(178 reference statements)
0
16
0
Order By: Relevance
“…When ATP is not consumed, the ATP/ADP ratio rises and respiration slows to state 4. Moreover, the studies by Kadenbach and colleagues have proposed that ATP exerts a negative allosteric modulation of the activity of complex IV . For all these reasons, a lower expenditure of ATP should not increase the amount of mitochondrial ATP.…”
Section: Resultsmentioning
confidence: 99%
“…When ATP is not consumed, the ATP/ADP ratio rises and respiration slows to state 4. Moreover, the studies by Kadenbach and colleagues have proposed that ATP exerts a negative allosteric modulation of the activity of complex IV . For all these reasons, a lower expenditure of ATP should not increase the amount of mitochondrial ATP.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that increased generation of ROS requires dynamic change of mitochondrial fission 38 , and Drp1 play a major role in regulating ROS production in apoptosis 39 . Previous studies showed that the induction of the peroxidase activity of Cyt-c is a key event in early apoptosis 40 , while the production of ROS, one of the primary factor of oxidative stress, is determined by Cyt-c-oxidase 41 . In this study, during AT-II cells of PQ intoxication, we detected the ROS production and release of Cyt-c and found that suppression of Drp1 by Mdivi-1 can block ROS generation and Cyt-c release.…”
Section: Discussionmentioning
confidence: 99%
“…is a rate-limiting step. Decreased expression of COX 4 results in an impaired Cytochrome c oxidase activity [ 4 , 5 ]. We hypothesize subsequent mitochondrial dysfunction associated with the formation of increased reactive oxygen species and inadequate maintenance of ATP levels when subunit 4 is reduced in the holoenzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic damage and reperfusion injury of myocardium proceed with an “Overspending ATP” and finally metabolic break down. The CytOx (complex IV) is directly involved and has the “center stage” [ 4 , 5 ]. This enzyme is considered to be the rate limiting step of electron transfer chain (ETC) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%